Enzootic bovine leukosis: performance of an indirect ELISA applied in serological diagnosis - González, Ester Teresa (2007)
Bovine Leukosis Virus (EBLV) is a widely distributed pathogen agent in the bovine population of many countries, especially in dairy cattle. Once the bovine is infected, it remains as a virus carrier for life and such state is correlated with a specific antibody detectable level. In this study the evaluation of an indirect ELISA (Leucokit-La Plata) to detect antibodies against EBLV is presented. Comparing it with the Immunodiffusion as gold standard test, the sensitivity is 98.93%, the specificity 79.74%, the negative predictive value 99.56% and the positive predictive value 61.26%. The correspondence between both tests is 83.9% which is similar to the result mentioned by other authors (82.2%). The concordance was evaluated by calculating Kappa and Youden's J coefficients, obtaining values classified as good for both coefficients. Comparing Leucokit-La Plata and another commercial reference kit (Chekit Leucotest Bommeli AG, Bern Switzerland), the sensitivity (97.05%), specificity (94.11%), negative predictive value (92.30%) and positive predictive value (97.77%), were obtained. Applying Kappa and Jouden's Index (J) coefficients an almost perfect concordance was obtained between both kits. The Leucokit-La Plata is appropriate to apply to the commercialization of live bovines to export, bovine selection for hemo-vaccines and the implementation of control and eradication programmes.